2012
DOI: 10.17221/5853-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

DNA integrity in fresh, chilled and frozen-thawed canine spermatozoa

Abstract: Sperm chromatin status in fresh dog semen and the effect of long-term storage of chilled and frozen dog semen on sperm chromatin integrity was assessed by the sperm chromatin structure assay (SCSA). In the first experiment, the chromatin integrity of fresh semen from 60 dogs with different historiy of fertility was compared with other sperm parameters (total sperm count, sperm motility, viability, acrosomal integrity and sperm morphology). Except for 15 dogs that had never mated before, all were used in breedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 48 publications
(53 reference statements)
4
27
0
3
Order By: Relevance
“…The SCD test was reported to be simple, highly reproducible and inexpensive technique, and the SCD results correlated with the SCSA results [28]. In the current paper, the DNA fragmentation indices were similar in fresh and frozen canine epididymal spermatozoa, which confirms the resilience of canine ejaculated sperm DNA to cold stress [12,15,16]. A progressive deterioration of DNA has been observed after exposure of fresh or thawed spermatozoa to different stressors (e.g., incubation time and temperature, toxicants, ROS) [21,29], indicating that thefreezing/thawing procedure facilitates the destabilization of the chromatin structure of spermatozoa [21].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The SCD test was reported to be simple, highly reproducible and inexpensive technique, and the SCD results correlated with the SCSA results [28]. In the current paper, the DNA fragmentation indices were similar in fresh and frozen canine epididymal spermatozoa, which confirms the resilience of canine ejaculated sperm DNA to cold stress [12,15,16]. A progressive deterioration of DNA has been observed after exposure of fresh or thawed spermatozoa to different stressors (e.g., incubation time and temperature, toxicants, ROS) [21,29], indicating that thefreezing/thawing procedure facilitates the destabilization of the chromatin structure of spermatozoa [21].…”
Section: Discussionsupporting
confidence: 76%
“…The impact of cryopreservation on sperm DNA integrity is still a controversial matter in mammals including dogs. Some authors showed that the freezing/thawing procedure did not produce significant adverse effects on chromatin status in canine ejaculated spermatozoa [12,15,16]. In contrast, Kim et al [14] found a higher DNA fragmentation in thawed compared to fresh spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, there was little difference between values of SDF obtained at the onset of incubation for fresh and frozen-thawed samples (either DMSO or SAR). Similar findings have been reported in stallion , ram , dog (Prinosilova et al 2012), koala (Johnston et al 2012b) and rainbow trout (Labbe et al 2001). Although the chromatin structure may appear unaltered by the cryopreservation process immediately upon thawing, the varying resistance of sperm DNA to stressors associated with post-thaw incubation ex vivo, particularly influences the longevity of sperm DNA quality (Gosálvez et al 2011a).…”
Section: Discussionsupporting
confidence: 60%
“…Sperm cryopreservation protocols that involve penetrating cryoprotectants developed for other amphibian species (Beesley et al 1998;Browne et al 1998;Costanzo et al 1998) samples showed a significant increase in SDF after 60 minutes of incubation, the proportion of sperm with SDF was still low, being less than 10%. Similarly, spermatozoa of numerous mammals including dog (Prinosilova et al 2012) and stallion ) retain a normal chromatin structure immediately after thawing (Gosálvez et al 2011b). Although Morrow et al…”
Section: Discussionmentioning
confidence: 99%